The validity of maternal and child perceptions of oral health status in 5- and 6-year-old children at Rajawali Catholic Kindergarten, Makassar: Validitas persepsi ibu dan anak terhadap Kesehatan gigi dan mulut anak usia 5 dan 6 tahun di TK Katolik Rajawali Makassar - Antolis, Jeannete Edita; Samad, Rasmidar; Anwar, Ayub Irmadani (Makassar Dental Journal PDGI Makassar, 2025)
To analyze the validity of maternal and child perceptions regarding the oral health status of 5- and 6-year-old children at Raja-wali Catholic Kindergarten in Makassar, a cross-sectional study with an analytic observational design was conducted. Data were collected through questionnaires (for mothers), interviews using facial expression cards (for children), and clinical exami-nations. The results showed a prevalence of early childhood caries (ECC) of 62.5%, with 34.6% of children presenting at least one instance of untreated caries-related complication. Mothers and children have a fair agreement regarding the child’s oral health (ICC=0.327). Maternal perception demonstrated a stronger correlation with clinical findings (r=0.692 for dmft; r=0.511 for pufa) compared to the child’s perception (r=0.290 and r=0.229, respectively). The area under the curve for maternal perception of treatment need reached 0.851 (dmft) and 0.789 (pufa), with the highest sensitivity recorded at 86.1% and specificity at 97.5%.